2004
DOI: 10.1111/j.1365-2273.2004.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature, humidity and peak inspiratory nasal flow on olfactory thresholds

Abstract: Temperature, humidity and nasal peak inspiratory flow rate (PIFR) are potential variables in the quantitative measurement of olfactory thresholds in the clinic. To date, these variables have not been properly evaluated with respect to olfactory perception, and therefore the aim of this study was to determine their effect on the thresholds. These variables were measured on 10 occasions in 10 subjects over a 10-week period. The results obtained were then subjected to statistical analysis using a linear mixed-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 12 publications
4
34
1
1
Order By: Relevance
“…It was assumed that normative values obtained in countries with more rough weather conditions would not be applicable in the mild Mediterranean climate as a result of a possible impact of the weather on the olfactory epithelium affecting the normal olfactory function. Although a weather effect on the olfaction has been occasionally hypothesized, 9 there are not presently clear data to support this hypothesis. Our present findings confirm the weather and environmental effect on olfactory performance, because our subjects obtained better results in all olfactory tests compared with the results obtained in other centers of northern and central Europe 7 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It was assumed that normative values obtained in countries with more rough weather conditions would not be applicable in the mild Mediterranean climate as a result of a possible impact of the weather on the olfactory epithelium affecting the normal olfactory function. Although a weather effect on the olfaction has been occasionally hypothesized, 9 there are not presently clear data to support this hypothesis. Our present findings confirm the weather and environmental effect on olfactory performance, because our subjects obtained better results in all olfactory tests compared with the results obtained in other centers of northern and central Europe 7 .…”
Section: Discussionmentioning
confidence: 95%
“…Athens, in central–southern Greece, and Alexandroupolis, in northern Greece, were the main locations in which our study was conducted, reflecting thus the average climate conditions of the country. The multicenter study of “Sniffin' Sticks” testing 9 that served as a model for the present investigation was conducted mainly in Germany with more than half of the patients examined in Erlangen‐Nurnberg. According to recent meteorologic data, 10,11 the mean weather variables in Athens were: maximum average monthly temperature 28° (July), minimum average monthly temperature 10° (January), and maximum average precipitation 66.0 mm (December).…”
Section: Discussionmentioning
confidence: 99%
“…Judah 12 suggested that a high level of humidity can be linked to bacterial growth which could decrease dog scent acuity, whereas other sources have proposed 25,26 that humidity can act to improve olfactory sensitivity. However, the findings of this study suggest that there was no significant relationship between relative humidity and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…With the apparatus setup determined it was then possible to examine the variables for olfactory testing. Temperature and humidity were assessed using a handheld thermohygrometer, peak inspiratory flow rate with a Youlton flow meter and patient scores for sense of smell, nasal symptoms, mood and alertness were recorded using visual analogue scores (18) . A suitable solvent was determined by a comparative study of potential solvents including propylene glycol and mineral oil (19) .…”
Section: Measurementsmentioning
confidence: 99%